1977
DOI: 10.1177/014662167700100106
|View full text |Cite
|
Sign up to set email alerts
|

Stylistic Components of Human Judgment: The Generality of Individual Differences

Abstract: In an effort to discover the generality of individual differences in judgmental processes, 12 potential styles were assessed from the predictions made by 86 judges across two or four replications of each of four judgmental tasks. The analyses focused on the internal consistency (across replica tions, within occasions), temporal stability (across occasions, within tasks), and intertask congruence of each of the judgmental variables. The findings suggested that five variables—linear predictability, judgmental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Correlations between measures of performance on general-knowledge questions and those same measures applied to basketball predictions showed substantial consistency in mean confidence, but only weak consistency in other components of judgment quality. These findings are consonant with the results of Ramanaiah and Goldberg (1977), who found more individual consistency for confidence than for 11 other components of judgment. Clearly, skill.in probability judgment is not a unitary trait.…”
Section: Individual Consistencysupporting
confidence: 86%
“…Correlations between measures of performance on general-knowledge questions and those same measures applied to basketball predictions showed substantial consistency in mean confidence, but only weak consistency in other components of judgment quality. These findings are consonant with the results of Ramanaiah and Goldberg (1977), who found more individual consistency for confidence than for 11 other components of judgment. Clearly, skill.in probability judgment is not a unitary trait.…”
Section: Individual Consistencysupporting
confidence: 86%
“…Often the perfectly reliable regression model performs better than the original judgments used to derive it (Armstrong 2001, Camerer 198 1 , Goldberg 1970). Cooksey, Freebody, and Bennett (1990) and Ramanaiah and Goldberg (1977) found that the reliability of bootstrapped judgments was higher than the reliability of the judgments themselves.…”
Section: Conditionsmentioning
confidence: 99%
“…When the adjusted R$,, value is estimated from their results, the value is .79, which is comparable to the average reliability of .72 obtained using repeated judgments. Ramanaiah and Goldberg (1977) report a correlation of .89 between reliability and the multiple correlation for 83 subjects, thus suggesting that the multiple correlation can be a reasonable indicator of reliability. …”
mentioning
confidence: 91%
“…New status and attention have been given to introspective and subjective "knowledge" (Natsoulas, 1970) and to clinical judgment, empathy, inference, and intuition (Christensen, 1974;Goldberg, 1970Goldberg, , 1972Ramanaian & Goldberg, 1977). With the Rorschach, too, clinical judgment and the subtle influence of intuition must be studied.…”
Section: Looking To the Futurementioning
confidence: 99%
“…But the intuitive need not be unreliable. It has been demonstrated that the intuitive clinical process and the stylistic components of clinical judgment do lend themselves to investigation and that methods may be devised toward improving the accuracy of clinical judgment (Christensen, 1974;Goldberg, 1970Goldberg, , 1972Ramanaian & Goldberg, 1977). It is my hope that we will devise similar research designs toward systematizing and communicating Rorschach ideology and skills.…”
Section: Looking To the Futurementioning
confidence: 99%